Réponses

Meilleure réponse !
2014-09-10T23:52:22+02:00
a) (3x+8)(x-5)=3x²-15x+8x-40=3x²-7x-40

b) 3x+8>0 ⇔ x>-8/3
x-5>0 ⇔ x>5
                                           -oo              -8/3              5                  +oo
3x+8                                              -                  +                  +
x-5                                                 -                  -                   +
(3x+8)(x-5)                                    +                  -                  +

Donc 3x²-7x-40≥0 si x≤-8/3  et si x≥5
Donc 3x²-7x≥40 ⇔ x∈]-oo;-8/3]U[5;+oo[